The literature review six steps to success - Machi, Lawrence A.; McEvoy, Brenda T. (Thousand Oaks, California Corwin, a SAGE Company, 2016)
Graduate students who turn in exceptional literature reviews are recognized as excellent critical thinkers as well as masters of academic argumentation, research writing, and academic writing. This six-step process pioneered by this book has made the task fluid and seamless.
Preface -- Introduction: Doing and producing a literature review -- Step one: select a topic -- Step two: develop the tools of argumentation -- Step three: search the literature -- Step four: survey the literature -- Step five: critique the literature -- Step six: write the review -- Glossary.
Includes bibliographical references and index.
Keywords: Research -- Methodology -- Study and teaching (Secondary) -- Handbooks, manuals, etc; Research -- Methodology -- Study and teaching (Higher) -- Handbooks, manuals, etc; Research -- Methodology -- Handbooks, manuals, etc